Effects of Dynamic Luminance Modulation on Visually Induced Self-Motion Perception: Observers' Perception of Illumination is Important in Perceiving Self-Motion. (February 2013) - Nakamura, Shinji; Seno, Takeharu; Ito, Hiroyuki; Sunaga, Shoji
Coherent luminance modulation of visual objects affects visually induced perception of self-motion (vection). The perceptual mechanism underlying the effects of dynamic luminance modulation were investigated with a visual stimulus simulating an external environment illuminated by a moving spotlight (the normal spotlight condition) or an inverted luminance version of it (the inverted luminance condition). Two psychophysical experiments indicated that vection was generally weakened in the inverted luminance condition. The results cannot be fully explained by the undesirable differences of luminosity within the experimental environment, and suggest that the contrast polarity of the visual stimulus has a significant impact on vection. Furthermore, the results show that the dynamic luminance variations weaken vection in the normal spotlight condition in which the observers perceived illumination modulations. In contrast, in the inverted luminance condition, in which the observers cannot perceive the illumination manipulation, the dynamic luminance variations may not impair vection, and may even be expected to strengthen vection, even though they shared similar global and systematic luminance variation with the normal spotlight condition. These experiments suggest that the observer's perception of illumination is a key factor in considering the effects of dynamic luminance modulation of the visual stimulus.